Critical role of interferons in gastrointestinal injury repair - Constance McElrath (Nature Portfolio, 2021)
Despite being prevalent yet well studied, ulcerative colitis still has poorly characterized pathophysiology. Here the authors use mouse colitis models to find that type I and III interferon (IFN) both contribute to ameliorating the disease, with IFN signaling in either the epithelial or hematopoietic compartment sufficient for this protective effect.